2013
DOI: 10.1016/j.compstruct.2013.04.010
|View full text |Cite
|
Sign up to set email alerts
|

An efficient finite element model for static and dynamic analyses of functionally graded piezoelectric beams

Abstract: International audienceno abstrac

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(32 citation statements)
references
References 40 publications
0
32
0
Order By: Relevance
“…Komijani et al [25] studied free vibration of FG piezoelectric beams with rectangular cross sections under in-plane thermal and electrical excitations in pre/postbuckling regimes. Lezgy-Nazargah et al [26] suggested an efficient three-nodded beam element model for static, free vibration and dynamic response of FGP material beams. Large amplitude free flexural vibration of shear deformable FG beams with surface-bonded piezoelectric layers subjected to thermo-piezoelectric loadings with random material properties presented by Shegokar and Lal [27].…”
Section: Introductionmentioning
confidence: 99%
“…Komijani et al [25] studied free vibration of FG piezoelectric beams with rectangular cross sections under in-plane thermal and electrical excitations in pre/postbuckling regimes. Lezgy-Nazargah et al [26] suggested an efficient three-nodded beam element model for static, free vibration and dynamic response of FGP material beams. Large amplitude free flexural vibration of shear deformable FG beams with surface-bonded piezoelectric layers subjected to thermo-piezoelectric loadings with random material properties presented by Shegokar and Lal [27].…”
Section: Introductionmentioning
confidence: 99%
“…The results were validated through interesting experiments. Lezgy-Nazargah et al [18] carried out static and dynamic analyses on piezoelectric beams by using a refined sinus model. The results have been found in good agreement with the reference solutions for various electrical and mechanical constrained conditions.…”
Section: Introductionmentioning
confidence: 99%
“…For the piezoelectric actuators made of di erent piezoelectric layers or identical piezoelectric layers with di erent poling directions, high stress concentrations usually appear in the layer interfaces under mechanical or electrical loading [14]. These stress concentrations lead to the initiation and propagation of micro-cracks near the interfaces of two bonded piezoelectric layers [15]. The lifetime and the reliability of these structures signi cantly reduce with the aforementioned drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…Doroushi et al [13] studied the free and forced vibration characteristics of an FGP beam under thermo-electro-mechanical loads using the higher-order shear deformation theory. Lezgy-Nazargah et al [15] proposed an e cient nite element model for static and dynamic analyses of FGP beams. They used an e cient three-nodded beam element which was based on a re ned sinus model.…”
Section: Introductionmentioning
confidence: 99%